2000
DOI: 10.1159/000013874
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch Negativity: Clinical and Other Applications

Abstract: The perspectives of application of the mismatch negativity (MMN), generated by the brain’s automatic response to change in auditory stimulation, are discussed. In light of the fact that the MMN (and its magnetic equivalent MMNm) currently provides the only objective measure of the accuracy of the central auditory function, these perspectives appear very promising. The MMN can be measured in the absence of attention and task requirements, which makes it particularly suitable for testing different clinical popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 146 publications
(81 citation statements)
references
References 78 publications
1
77
0
3
Order By: Relevance
“…Two lines of evidence suggest that this period entails the encoding of cortical representations of auditory space, rather than higher order process. First, it corresponds to the time period over which the MMN response has been observed to changes in the position of a sequence of sounds, particularly when behavioral discrimination is difficult and/or when there is minimal separation in terms of the physical features of the stimuli (Näätänen and Escera, 2000). We interpret the response change during the MMN temporal window as indicating that traininginduced plasticity of the cortical representations of the two positions and/or the cortical mechanisms involved in position discrimination (Näätänen et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Two lines of evidence suggest that this period entails the encoding of cortical representations of auditory space, rather than higher order process. First, it corresponds to the time period over which the MMN response has been observed to changes in the position of a sequence of sounds, particularly when behavioral discrimination is difficult and/or when there is minimal separation in terms of the physical features of the stimuli (Näätänen and Escera, 2000). We interpret the response change during the MMN temporal window as indicating that traininginduced plasticity of the cortical representations of the two positions and/or the cortical mechanisms involved in position discrimination (Näätänen et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…In our experiments, we thus focused on automatic or task-irrelevant novelty detection in the auditory domain (and its plasticity related to musical training), because automaticity is an important property of an efficient novelty discrimination system allowing the brain to rapidly and effortlessly detect change in the environment (Sokolov, 1963;Brown and Bashir, 2002;Yamaguchi et al, 2004;Kumaran and Maguire, 2007b). Note that this approach is similar to experimental conditions commonly used in electrophysiological studies to test for the neural correlates of preattentive oddball detection in the acoustic domain (for review, see Näätänen and Escera, 2000;Näätänen et al, 2001) and to identify functional differences in automatic auditory processing in musicians and nonmusicians on a cortical (for review, see Munte et al, 2002) and subcortical level (Parbery-Clark et al, 2009). …”
Section: Auditory Stimulation During Functional Imagingmentioning
confidence: 99%
“…Our finding showed that the MMN response elicited by the SNHL subjects was smaller (almost half of the activation) and recorded at longer latencies on both CVs speech stimuli compared to that of the control group. In other words, the difference in MMN auditory response of hearing impaired subjects was found to reflect not only the detection of speech phonologic features, but also revealed the anomalies in physiological measure of automatic discriminant ability involving central processing in audition (Näätänen 1995;Näätänen & Escera 2000).…”
Section: Implication Of Speech Stimulus On Mismatch Negativity (Mmn) mentioning
confidence: 99%